IDENTIFICATION, CHARACTERIZATION AND EVALUATION OF FOUR WILD SPECIES OF PIGEONPEA AS A STEP TOWARDS INTERSPECIFIC HYBRIDIZATION - JAIN, JAAGRATI (Annals of Agricultural Research, 2014)
Characterization and preliminary evaluation of four wild species and four cultivated types was carried out under screen house conditions during 2001-2003, at IARI, New Delhi, using Â randomized block design. Variation was observed in number of promary and secondary branches, leaflet shape, pod form, base seed colour, seed shape and number of seeds/pod within cvs . Combined susceptibility to insect pests like pod borer and pod fly was found to be more fifty percent (intermediate to high as per descriptors) in four cvs during 2001-2004 based on field screening using RBD with no plant protection measures.